The disparity mutagenesis model predicts rescue of living things from catastrophic errors - Furusawa, Mitsuru (Frontiers in Genetics, 2014)
In animals including humans, mutation rates per generation will exceed a perceived threshold, which should result in an excessive genetic load. Despite this, they have survived without extinction. This is a perplexing problem for human genetics, arising at the end of the last century, and to date still does not have a fully satisfactory explanation. Shortly after we proposed the disparity theory of evolution in 1992, the disparity mutagenesis model was proposed, which forms the basis for an explanation for an acceleration of evolution and species survival. This model predicts a significant increase of the mutation threshold values if there is a high enough fidelity difference in replication between the lagging and leading strands. When applied to biological evolution, the model predicts that living things, including humans, might overcome the lethal effect of accumulated deleterious mutations and be able to survive. Artificially-prepared mutator strains of microorganisms, in which an enhanced lagging-strand-biased mutagenesis was introduced, showed unexpectedly high adaptability to severe environments. The implications of the striking behaviors shown by these disparity mutators will be discussed in relation to how living things with high mutation rates can avoid the self-defeating risk of excess mutations.